Leadership styles adopted in selected non-bank financial institutions in the Cape Coast metropolis, Ghana - Asiedu, Leticia Anane; Andoh-Kumi, Fiifi; Koomson, Samuel (Utan Kayu Publishing, 2022)
This paper seeks to assess the leadership styles exhibited in selected non-bank financial institutions in the Cape Coast Metropolis, and, to further investigate the reasons for adopting such leadership style(s). A questionnaire was utilized. Responses were sought from both leaders and their subordinates. A census was used to select the leaders, while simple random sampling technique was used to select subordinates. The results showed that transformational and transactional leadership styles were often adopted by the leaders, with transformational leadership style being the dominant. Laissez-faire leadership style was the least adopted. The results also showed that organizational culture, attitude of staff, and nature of work were the underlying reasons for adopting both transformational and transactional leadership styles. The study concluded that leaders of non-bank financial institutions in the Cape Coast Metropolis used a mixture transformational and transactional leadership styles in their day-to-day operations due to their organisational culture, attitude of staff, and nature of their work.